Lithium-ion battery rightsizing technologies for future road transport applications - Marecki, Malcolm (2024)
The advancement of Lithium-Ion batteries has led to significant recent growth and development in electrified road transport vehicles. Lithium-Ion technology has enabled battery storage to offer higher energy density, power density and faster recharging capabilities. Electrified vehicles (utilising lithium-Ion batteries) have the potential to substantially mitigate the harmful effects of vehicle emissions (including greenhouse gas emissions and toxic pollutants which negatively affect global climate and human health). The work reported in this thesis has involved investigation of different road transport solutions overcoming some of the remaining challenges of lithium-Ion electrification. Both full electric and hybrid vehicle platforms have been analysed to develop different solutions suitable for different markets and consumers (optimising road transport powertrain systems for different use cases allowing for as many users as possible to transition to electrified transport as well as minimising the net greenhouse gas emissions effect). The work has involved both experimental and analytical research to investigate road transport powertrain systems. Both physical rolling road (lab based) and analytical models of vehicle drive cycles have been used to evaluate the energy impacts of different vehicles (ranging from B-segment cars to commercial trucks). Further research was conducted to understand and optimise the characteristics of powertrain subsystems. CFD tools were utilised to evaluate battery thermal management systems (BTMS). A next generation battery system incorporating a novel partially immersion cooled BTMS has been designed. This solution enables vehicles to have long-range capabilities (480 km), ultra-fast charging (>150 kW) and long-term battery state of health and safety features. The novel battery system has been designed to integrate into the vehicle floor-pan of a 2021 Model Year BMW i3 (upgrading the existing vehicle battery architecture) however the solution concept is scalable and flexible allowing adaptation to different vehicle geometries.